Psychological Specificity of Persistence in Students - S V Baranova (RUDN Journal of Psychology and Pedagogics, 2014)
The article is devoted to the problem of revealing the psychological features of persistence within the framework of the systemic-functional approach developed by A. I Krupnov. The results of the empirical research of the psychological structure of persistence and personality traits of students are considered.